Navigating the margins: How a culturally responsive and relevant pedagogical framework can inform the creation of a positive developmental context for African American male youth - Craven , Krista; McCormack , Mark; Brinkley-Rubinstein , Lauren (Journal of Interdisciplinary Studies in Education, 2014)
This article explores how a program that provides race-specific training and mentoring to African American male adolescents aligns with the principles of culturally relevant and responsive pedagogy. The paper draws on data from qualitative fieldwork conducted in 2011 and 2012 with 16 youth participants of an out-of-school program called the STRIVE Empowerment Program for African American Boys. Findings suggest that while STRIVE attempts to promote the positive development of African American male youth in a culturally relevant and responsive manner, the program is structured in such a fashion that it may complicate this process and, perhaps, even negate key outcomes associated with positive developmental outcomes for the adolescents it serves.